Non-holomorphic modular A 5 symmetry for lepton masses and mixing - Cai-Chang Li; Jun-Nan Lu; Gui-Jun Ding (Journal of High Energy Physics)
Abstract We perform a comprehensive bottom-up study of all the simplest lepton models based on non-holomorphic A 5 modular flavor symmetry, in which neutrinos are assumed to be Majorana particles and their masses are generated by the Weinberg operator or the type I seesaw mechanism. In the case that the generalized CP (gCP) symmetry is not considered, we find that 21 Weinberg operator models and 174 seesaw models can accommodate the experimental data in lepton sector, and all of them depend on six dimensionless free parameters and two overall scales. If gCP symmetry compatible with A 5 modular symmetry is imposed, one more free parameter would be reduced. Then only 4 of the 21 Weinberg operator models and 100 of the 174 seesaw models agree with the experimental data on lepton masses and mixing parameters. Furthermore, we perform a detailed numerical analysis for two example models for illustration.